Manufacturing and evaluation of Chitosan, PVA and Aloe Vera hydrogels for skin applications (2017)
ABSTRACT: The aim of this research was to develop membranes of polyvinyl alcohol (PVA) and chitosan (CH), capable of absorbing an Aloe Vera solution and gradually releasing to accelerate wound healing. The methodology involved varying the membrane’s composition using Chitosan and Polyvinyl Alcohol at 5 and 10% w/v, and implementing different PVA/CH relations of 30/70, 50/50 and 70/30 (v/v) and embed them in a 2% (v/v) Aloe Vera solution to create hydrogels. Once hydrogels were obtained, they were characterized by Infrared Spectroscopy and Scanning Electronic Microscopy, and evaluated by mechanical and absorption tests as well as bactericide activity assays. The crosslinking degree between PVA/CH allowed obtaining a matrix with high absorption capacity and with gradual release of Aloe Vera, with mechanical properties and dimensional stability even after rehydration. Bactericide assays showed chitosan and Aloe Vera protective activity, which indicates this compound may be suitable for applications that help in wound healing.